Essay-BR: a Brazilian Corpus of Essays - Marinho, Jeziel C.; Anchiêta, Rafael T.; Moura, Raimundo S. (Anais do Dataset Showcase Workshop (DSW); 2021: Anais do III Dataset Showcase WorkshopDO - 10.5753/dsw.2021.17414, 2021)
Automatic Essay Scoring (AES) is the computer technology that evaluates and scores the written essays, aiming to provide computational models to grade essays automatically or with minimal human involvement. While there are several AES studies in a variety of languages, few of them are focused on the Portuguese language. The main reason is the lack of a corpus with manually graded essays. We create a large corpus with several essays written by Brazilian high school students on an online platform in order to bridge this gap. All of the essays are argumentative and were scored across five competences by experts. Moreover, we conducted an experiment on the created corpus and showed challenges posed by the Portuguese language. Our corpus is publicly available at https://github.com/rafaelanchieta/essay .